Ethical Issues in Cybermedicine. - Paris, John J. (America Magazine: The Jesuit Review of Faith & Culture, 2001)
Deals with the ethical issues involving cybermedicine. Use of the Internet as a form of communication with physicians; Impact of electronic commerce to the medical industry; Changes brought by the Internet; Areas of ethical concern involving health resources on the Internet.